PEMBUATAN LKS FISIKA BERBASIS ICT DENGAN MENGINTEGRASIKAN NILAI PENDIDIKAN KARAKTER KELAS X SEMESTER 2 - Ollyvia Theresia Amelia (PILLAR OF PHYSICS EDUCATION, 2013)
Abstract – Integration of character values in learning process are important to reach the purpose of national learning. One solution to integrate the character values in learning process through worksheet based on ICT. The purpose of this research is to produce worksheet based on ICT in Physics subject that integrate of character value  that valid, practice, and effective to use in Physics learning process. Object of this research is worksheet based on ICT integrate education character value. The instruments are used to collect the data in this research are: validity sheet, practicality sheet, learning outcome test sheet, and observation character value sheet. Based on analyze of the data, there are four result of this research. First, worksheet has high validation score 84.55. Second, design worksheet based on ICT consist of home, introduction, competence, worksheet, evaluation, and download. Third, the value of practicality of worksheet based on ICT according to teachers and students are 81,81 and 88,28. Fourth, worksheet based on ICT effectives to increase learning outcomes and grow up the character value of students. Keywords – Worksheet, ICT, Character Value, Validity, Practicality, Effectivity